2018
DOI: 10.1016/j.nlm.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Housing and testing in mixed-sex rooms increases motivation and accuracy during operant testing in both male and female mice

Abstract: Operant behavior tasks are widely used in neuroscience research, but little is known about how variables such as housing and testing conditions affect rodent operant performance. We have previously observed differences in operant performance in male and female mice depending on whether mice were housed and tested in rooms containing only one sex versus rooms containing both sexes. Here, male and female mice in either single-sex or mixed sex housing rooms were trained on fixed ratio 1 (FR1) and progressive rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These and related observations have raised concerns about sanitation practices in mouse husbandry that can alter pheromonal signaling and potentially cause confounding effects in the research. Even the organization of a mouse room, segregating male and female mice, could have a significant effect on experimental results ( Bind et al, 2013 ; Lloyd et al, 2018 ). Evidence regarding the effects of human pheromones is highly controversial, but a recent paper suggests that this is one area where mice and humans might have rather distinct environmentally mediated communication mechanisms ( Hare et al, 2017 ).…”
Section: Effects Of Environment On Ethologically Appropriate Behaviormentioning
confidence: 99%
“…These and related observations have raised concerns about sanitation practices in mouse husbandry that can alter pheromonal signaling and potentially cause confounding effects in the research. Even the organization of a mouse room, segregating male and female mice, could have a significant effect on experimental results ( Bind et al, 2013 ; Lloyd et al, 2018 ). Evidence regarding the effects of human pheromones is highly controversial, but a recent paper suggests that this is one area where mice and humans might have rather distinct environmentally mediated communication mechanisms ( Hare et al, 2017 ).…”
Section: Effects Of Environment On Ethologically Appropriate Behaviormentioning
confidence: 99%
“…While more limited in use to date than the CB task, non-touchscreen versions of PR have provided some potential insights into husbandry practices. For example, housing conditions can impact PR performance in rats (mixed-sex vs. single-sex holding rooms 172 ) and in NHPs (single housing vs. pair-housing 173 ). These studies support the viability of using the PR schedule as a tool to assess the effect of husbandry-related factors on laboratory animal welfare.…”
Section: Touchscreens As Animal Welfare Evaluation Toolsmentioning
confidence: 99%
“…Most of the animal studies that use operant tasks are performed in male rodents, although there is some literature on performance of female rodents in operant tasks. Thus, it has been observed that female mice lever-press less in a progressive ratio operant task (Lloyd et al, 2018), and the same pattern is observed in female rats using fixed ratios (van Haaren et al, 1990). However, so far there are no published studies assessing female performance in effort-based decision-making tasks.…”
Section: Discussionmentioning
confidence: 85%